The south atlantic aerial crossing of joão ribeiro de barros in 1927 - Marques, Flávio D.; Vasconcellos, Rui M. G. [UNESP] (American Institute of Aeronautics and Astronautics (AIAA), 2019)
The history of the Brazilian aviator João Ribeiro de Barros is taken as an example of the significant efforts to cross the South Atlantic Ocean during the 1920s. He and his crew were not the first to perform such adventure, but many others pioneers also tried. Some of them died during their attempt. The conquering of the South Atlantic by air represented an enormous breakthrough in aviation and allowed the integration of South America with the European countries. By establishing such aerial routes, significant trade and communication links were enhanced. Captain Barros’ raid was fraught with difficulties, endangered by sabotage, arrest, and malaria. He succeeded in crossing the most extended leg in the Atlantic arriving in the Brazilian territory on April 27th, 1927. With this, captain Barros was the first pilot from the Americas to make an aerial non-stop crossing of the Atlantic Ocean without the backup from ships.